2007
DOI: 10.1111/j.1365-2788.2006.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐determination, social abilities and the quality of life of people with intellectual disability

Abstract: These findings contribute to an emerging knowledge base pertaining to the role of intraindividual and environmental factors in self-determination and QoL. In general, the study replicated findings pertaining to the relative contribution of intelligence to self-determination and QoL, added information about the potential contribution of social abilities, and pointed to the potentially important role of opportunities to make choices as a particularly important aspect of becoming more self-determined, at least in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
193
0
30

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(242 citation statements)
references
References 23 publications
19
193
0
30
Order By: Relevance
“…This stance reflects a need to respond to the historical experiences of many people with disabilities in being excluded from decision making [72] and research highlighting the role of decision-making participation in identity development and personal well-being. [73][74][75] By exploring the experiences of adults with severe TBI, this study provides further evidence of the importance of decision-making participation through its contribution to the dynamic process of self-conceptualization after injury.…”
Section: Discussionmentioning
confidence: 99%
“…This stance reflects a need to respond to the historical experiences of many people with disabilities in being excluded from decision making [72] and research highlighting the role of decision-making participation in identity development and personal well-being. [73][74][75] By exploring the experiences of adults with severe TBI, this study provides further evidence of the importance of decision-making participation through its contribution to the dynamic process of self-conceptualization after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst sense of belonging and social acceptance are integral to obtaining a realistic and positive self-image (Nota et al 2007;Wehman et al 2009), for people with ASD this concept might be determined to a large extent by personal preference for routine or individual challenges posed by sensory and social interaction difficulties. Given that such challenges dictate the rhythm of daily lives of adults with ASD, it would seem that there is a significant discrepancy in constructing the current notion of autonomy, in that it does not allow for free expression of individual perspectives or preferences in one's closest environment despite adults with ASD being expected to do so when making life choices.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomy is essential in several important areas of life, including problem solving, decision-making, goal setting, as well as obtaining a realistic and positive self-image (Nota et al 2007). Expressing personal preferences, making autonomous decisions based on those preferences, and assuming personal responsibility for the course of one's choices are expressions of freedoms that are assigned significant value in market-oriented societies.…”
Section: Discussionmentioning
confidence: 99%
“…gender) or experience with selfdetermination and family support for self-determination within or across cultures. Given previous research (Nota et al, 2007;Shogren et al, 2006) that has suggested these variables may influence student self-determination, further research is needed to explore the influence of these characteristics across cultures. Second, our sample was limited to Italian and American adolescents, future research including a more diverse sample of nationalities is needed.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Shogren (2011) explored the literature on culture and the fSDT, and found theoretical and empirical research examining the expression of self-determined behaviour in Diné cultures (Navajo) (Frankland, Turnbull, Wehmeyer, & Blackmountain, 2004), Korean (Lee & Wehmeyer, 2004), Japanese (Ohtake & Wehmeyer, 2004), Chinese (Zhang, Wehmeyer, & Chen, 2005), as well as diverse cultures within the United States (Trainor, 2005;Valenzuela & Martin, 2005). Researchers in Italy (Nota, Ferrari, Soresi, & Wehmeyer, 2007) and Belgium (Lachapelle et al, 2005) have also explored self-determination and its relationship with other constructs. While this body of research suggests universal aspects of the self-determination construct, it also highlights differences in the specific ways that selfdetermined behaviour may be expressed in different cultures.…”
Section: Introductionmentioning
confidence: 99%